Indoor Positioning Using WSN and INS Sensor Fusion - Akeila, Ehad; Salcic, Zoran; Swain, Akshya (International Journal of Sensors Wireless Communications and Control, 2014)
This paper proposes a new method for enhancing the accuracy and availability of positioning in indoor environment based on fusion of the positioning results obtained from two sensing technologies, Inertial Navigation System (INS) and Wireless Sensor Network (WSN) (in this case Bluetooth- based positioning system). The performance of each individual sensing technology has been optimised first using new positioning methods before performing the fusion of results. The fusion is achieved by the utilisation of two fusion filters, particle filter and Extended Kalman filter, and is thoroughly tested using a portable data acquisition unit which is specially designed for that purpose. Detailed analysis and comparison of the performance between particle filter and Extended Kalman filter has been performed. Results show that the proposed fusion method reduces the errors compared to single sensing technology and the mean distance error of the final fused system is maintained below 1 metre using either of the two filters.
Keywords: Kalman Filter